Implementasi Pendekatan Humanistik terhadap Pemahaman Mahasiswa pada Materi Nilai Islam Rahmatan Lil‘Alamin di Institut Agama Islam Al-Amanah Jeneponto - Rudi Hartono; Syahrianti Syahrianti; Rostinah Rostinah (ALSYS, 2026)
Although the humanistic approach to learning has attracted considerable attention in educational research, studies that specifically examine its implementation in shaping students’ understanding of Islam as Rahmatan lil ‘Alamin within Islamic religious higher education institutions remain limited. This study aimed to explore the implementation of the humanistic approach in relation to students’ understanding of the formation of Islam Rahmatan lil ‘Alamin character at Institut Agama Islam Al-Amanah Jeneponto. A qualitative case study design was employed, involving 15 participants who were students of Institut Agama Islam Al-Amanah Jeneponto selected through purposive sampling. Data were collected through in-depth interviews, observation of learning processes, and documentation studies, and were analyzed using thematic analysis. The findings indicate that the implementation of the humanistic approach enhanced students’ understanding of Islamic values that are humanistic, moderate, tolerant, and humanity-oriented, as reflected in their attitudes, patterns of social interaction, and academic behavior. These findings contribute to the development of humanistic learning theory in the context of Islamic education and broaden understanding of the formation of Islam Rahmatan lil ‘Alamin character in higher education. The study concludes by underscoring the importance of the humanistic approach as an effective Islamic Religious Education learning strategy for shaping an inclusive Islamic character, and recommends that lecturers and educational managers systematically integrate this approach into curricula and instructional practices. The implications of this research include theoretical contributions to enriching the literature on humanistic learning grounded in Islamic education and practical implications for Islamic higher education institutions in strengthening students’ character, while also opening avenues for further research on quantitatively measuring the impact of the humanistic approach on students’ attitudes and character.